Regenerative medicine: Historical roots and potential strategies in modern medicine. Issue 3 (September 2015) - Sampogna, Gianluca; Guraya, Salman Yousuf; Forgione, Antonello
Abstract: Regenerative medicine is a distinct major advancement in medical treatment which is based on the principles of stem cell technology and tissue engineering in order to replace or regenerate human tissues and organs and restore their functions. After many years of basic research, this approach is beginning to represent a valuable treatment option for acute injuries, chronic diseases and congenital malformations. Nevertheless, it is a little known field of research. The purpose of this review is to convey the state of the art in regenerative medicine in terms of historical steps, used strategies and pressing problems to solve in the future. This review represents a good starting point for more in-depth studies and personal research projects.